Procedimiento de imbricación de la fascia transversalis en la herniorrafia inguinal - Croci, Fabio; Kamaid, Emil; Gastambide, Carmelo; Pérez Penco, Ernesto; Cordal, Adriana (Cirugía del Uruguay, 1984)
Authors present the procedure for imbrication of the fascia transversalis in the repair of inguinal hernia, based on 36 cases operated by this technique. Analyzed are its bases, technique, indications and results.